Screening time product placement in the top 3 grossing films of the 2013 MMFF - Moralidad, Noemie Marie
Product placement is the purposeful incorporation of commercial content into non-commercial settings, that is, a product plug generated through the combination of advertising and entertainment. While product placement is riskier than conventional advertising, it is becoming a common practice to place products and brands into mainstream media including films, broadcast and cable television programs, computer and video games, blogs, music videos/DVDs, magazines, books, comics, radio, internet, and mobile phones. To reach retreating audiences, advertisers use product placements increasingly in clever, effective ways that do not cost too much. The purpose of this qualitative and quantitative study combined is to examine the genral product category and the physical characteristics of product placement injected in the 2013 Metro Manila Film Festival top three highest grossing films, and to answer if these characteristics are interrelated to each other.